Phycoerythrin Peptide from Pyropia yezoensis Alleviates Endoplasmic Reticulum Stress Caused by Perfluorooctane Sulfonate-Induced Calcium Dysregulation - Oh, Jeong Hwan (Mar Drugs, 2018)
Perfluorooctane sulfonate (PFOS), a stable fluorosurfactant, causes endoplasmic reticulum (ER) stress in the brain. This study was designed to investigate whether a phycoerythrin-derived peptide of Pyropia yezoensis (PYP) reduces PFOS-induced ER stress associated with calcium dysregulation. The protective effects of PYP were determined by cell viability, immunoblotting for ER stress response protein glucose-regulated protein 78 (GRP78) and calcium-dependent protein kinases in rat frontal cortical neurons. PFOS-induced decrease in cell viability was attenuated by PYP pretreatment (1 µg/mL) for 24 h, which was downregulated by inhibiting tropomyosin-receptor kinase B (TrkB). PYP pretreatment downregulated the increase in intracellular calcium levels and phosphorylation of calcium/calmodulin-dependent protein kinase II and c-Jun N-terminal kinase which are associated with a PFOS-induced increase in GRP78. The PFOS-induced increase in GRP78 was downregulated via activation of TrkB receptor-linked extracellular signal-regulated kinases 1/2 (ERK1/2) by PYP pretreatment. Moreover, PYP microinjections (1 µg/kg, 0.54 nmol) attenuated the GRP78 expression in rat prefrontal cortex caused by PFOS (10 mg/kg) exposure for 2 weeks. These findings demonstrate that PYP enhances frontal cortical neuron viability via activation of TrkB receptor-ERK1/2 signaling and attenuation of ER stress in rat prefrontal cortex against PFOS exposure, suggesting that PYP might prevent neuronal dysfunctions caused by PFOS-induced ER stress.